Implementasi Hukum terhadap Tindak Pidana Scammer - Yohanes Reston N.A Laia; Rahmayanti Rahmayanti; Sari Sania Tampubolon; Alex Sokhian Gea; Sudarno Hariadi Nasution (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Law enforcement is an effort to realize the ideals of law to create justice, benefit and legal certainty in reality. The crime of online fraud based on scammers is a cyber crime, the regulation is regulated in Article 378 of the Criminal Code. From year to year the number of scammer-based online fraud crimes is increasing as evidenced by community reports every year and even every week there must be victims of fraud crimes committed in cyberspace, but the number of settlements is very small, this indicates a problem, both internally and externally, so that law enforcement which is the benchmark for the effectiveness of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions, The author is interested in conducting a qualitative research method, to find various reading literature related to the application of law to criminal acts of fraud committed online or can be referred to as scammers, this research aims to find legal certainty and benefits for people who feel harmed.